Usaha home indusry teh BADAK (Bawang Dayak) Eleutherine americana Merr pada komunitas BIJAK (Bunda Inovatif Jayapura Aktif Kreatif) di Kampung Jayapura, Kecamatan Bungaraya, Kabupaten Siak - Yustina Yustina; Silvia Reni Yenti; Hendra Taufik; Syapsan Syapsan; Nita Nita (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2019)
The service activities in Jayapura village were held from October 2018 to May 2019 in Jayapura Village, Siak Regency, aims to cultivate dayak onions by using organic waste compost and processing it into BADAK Tea (Dayak Onion) as an opportunity for home industry among PKK members. Method of activities through socialization, training, mentoring and field monitoring. The results ofactivities socialization and trainingare obtained; 96% of participants received knowledge of onioncultivation dayak (BADAK), 91% of participants were knowledgeable about the efficacy and benefits of BADAK, and 33% of participantswere interested in cultivating, and those skilled in cultivating BADAK increased from 20 people to 40 people. From the assistance obtained 100% of prticipants have used compost in cultivation and the BADAK yields increased 100%. Next, the yields are used 50% to be used as seed stock and 50% of the yields (profits) are used for the services of BIJAK community (Innovative Mother of Jayapura Active and Creative). The obstacle of the activity is to change the behavior of participants in teamwork and thethinking process ofthat is more likely to sell their crops without processing them intotea products BADAK.